2019
DOI: 10.1021/acs.jpclett.9b02932
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Monitoring Excitation Dynamics of Human Telomeric Guanine Quadruplexes: Effect of Folding Topology, Metal Cation, and Confinement by Nanocavity Water Pool

Abstract: Guanine(G)-rich human telomeric (HT) DNA repeats, crucial to maintenance of genome stability, readily form G-quadruplexes (GQs) with various folding topologies. Research on excitation dynamics of HT-GQs is, however, scarce. Herein, we report a femtosecond time-resolved fluorescence coupled with transient absorption investigation on HT-GQ with the baskettype structure in Na + solution. The result unveils an unusual multichannel nonradiative mechanism dominated by states with varying character of charge transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(70 citation statements)
references
References 45 publications
9
60
1
Order By: Relevance
“…In the frame of this scenario, K + ions, which are larger and less mobile than Na + , should hinder the stabilization of CT states, favoring charge separation instead. This is corroborated by a recent time-resolved study focusing on the excited states, which shows that the transient absorption of CT states is more important for TEL21/Na + compared to TEL21/K + [22].…”
Section: Photo-ionizationsupporting
confidence: 73%
See 1 more Smart Citation
“…In the frame of this scenario, K + ions, which are larger and less mobile than Na + , should hinder the stabilization of CT states, favoring charge separation instead. This is corroborated by a recent time-resolved study focusing on the excited states, which shows that the transient absorption of CT states is more important for TEL21/Na + compared to TEL21/K + [22].…”
Section: Photo-ionizationsupporting
confidence: 73%
“…The mechanism proposed to explain the φ 1 enhancement is related to a non-vertical electron photo-detachment and is described in reference [11]. Briefly, charge transfer (CT) states are formed during the excited state relaxation [20][21][22]. A small fraction of the CT states may undergo charge migration, followed by charge separation.…”
Section: Photo-ionizationmentioning
confidence: 99%
“…Population of excited CT states both in duplexes [42][43][44] and G4 41,45,46 is well documented. The occurrence of charge separation along DNA strands has also been reported.…”
Section: Evidence For a Non-vertical Photo-ionization Mechanism?mentioning
confidence: 99%
“…39 In the frame of such a scenario, Na + cations, smaller and more mobile than K + , 40 allow the geometrical arrangement accompanying stabilization of CT states 41 and, hence, reducing the probability of charge separation. Population of excited CT states both in duplexes 42−44 and G4 41,45,46 is well documented. The occurrence of charge separation along DNA strands has also been reported.…”
Section: ■ Evidence For a Nonvertical Photoionization Mechanism?mentioning
confidence: 99%
“…Femtosecond studies detected the population of CT states in telomeric G4. It was also shown that the excited state relaxation pattern remains the same in reversed micelles, mimicking the crowding conditions in cells . QM calculations performed for such G4 showed that CT states may be formed between a T in the loop and a G in the core, but experiments have not disentangled this type of mixed CT states from those involving two guanines .…”
mentioning
confidence: 99%